Achieving the interpretive culture in the light of modern times - Al Deek, Mohammed Yousef Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
In this research, I have highlighted issues worthy of attention, as a new term which is the explanatory culture, which is based in general on the general knowledge of interpretation other than specialized reading, and this knowledge depends on knowledge of the principles and rules of interpretation, and can be measured by identifying the most important general features of knowledge: the most important books of interpretation, And to see the availability of the books of the science of the Koran, and the ability to refer to the various interpretations, and citing the Koranic texts in various fields, and in order to achieve this culture must be cited Koranic verses by suggesting in the curricula of education and the use of means Various technological, employing the so-called Baltvseralttabiqi through different models of the verses of the Koran, and the use of the best books facilitating easy, and programs televised and dealing with Quranic stories, employing Arabic poetry in the matching interpretation of the words of the Qur’an, and finally holding seminars and competitions related.